Soil physico-chemical properties in jhum fields and forests of Sagalee and Namsai region in Arunachal Pradesh - Arunachalam, Ayyanadar (Indian Journal of Agroforestry, 2022)
A study was conducted to compare the soil properties of shifting agricultural systems in two geographically isolated zones in the state Arunachal Pradesh. The soils were sandy loam and loamy sand in nature. Water holding capacity (WHC) of the topsoil layer was always greater as compared to the lower depth in all the sites. Soil pH did not show much seasonal variation, except during the rainy season (April and October), where the value was low in the subsurface (15-30 cm) layer. Soil organic C (SOC) decreased with increasing soil depth. As expected, it was highest in the forest as compared to the jhum cultivation fields in both eastern and western Arunachal Himalaya. Site-wise variations in soil organic carbon (SOC) was significant (P